Situation Report: Poland, 24 August 1961 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. GDR Envoys to Tito Berlin/German Question Four Shifts for Foundry Work Tourists Russian Liberation Anniversary Air Force Day Agricultural Development Fund Cernik in Silesia Foreign Funds Agricultural Schools